Gimeracil enhances the antitumor effect of cisplatin in oral squamous cell carcinoma cells in vitro and in vivo - Harada, Koji (Oncol Lett, 2017)
Gimeracil or 5-chloro-2,4-dihydroxypyridine (CDHP) enhances the antitumor effects of 5-fluorouracil (5-FU) by inhibiting dihydropyrimidine dehydrogenase (DPD), which is involved in the degradation of 5-FU. CDHP, as part of a combination therapy, was also reported to exert a radiosensitizing effect. Therefore, CDHP may have underlying mechanisms of action other than DPD inhibition. The focus of the present study was to investigate the antitumor effects of CDHP and cisplatin (CDDP) combination treatment in vitro and in vivo against oral squamous cell carcinoma (OSCC) tumors. The inhibitory growth effects of CDHP and/or CDDP treatment on SAS and HSC2 cells were examined using an MTT assay. The expression levels of DNA double strand break repair proteins, including Ku70, DNA-dependent-protein kinase catalytic subunit (DNA-PKcs), Rad50 and Rad51 in CDHP and/or CDDP-treated cells were detected using western blotting. Nude mice with SAS or HSC2 tumors were treated with CDHP (administered orally 7 times/week) and/or CDDP (administered by intraperitoneal injection once/week) for 2 weeks. Combined treatment of CDHP and CDDP significantly suppressed the growth of SAS and HSC2 cells in vitro and that of tumors in vivo compared with the effects caused by single drug only or control treatments. Western blotting demonstrated that the expression levels of Ku70, DNA-PKcs, Rad50 and Rad51 were downregulated in cells treated with CDHP and CDDP combination treatment. Immunohistochemistry also identified that the expression of DNA double strand break repair proteins was downregulated in tumors treated with CDHP and CDDP combination treatment compared with that of tumors treated with CDDP alone or control. The results of the current study suggest that CDHP may be responsible for enhancing the antitumor effects of CDDP by suppressing the DNA double strand break repair system. Therefore, the combination of CDHP and CDDP may be a potential effective option for OSCC treatment.